WingAnalogy: a computer vision-based tool for automated insect wing asymmetry and morphometry analysis - Shahab Eshghi; Hamed Rajabi; Матушкіна, Наталія Олександрівна; Lisa Claußen; Johannes Poser; Thies H. Büscher; Stanislav N. Gorb (Springer Science and Business Media LLC, 2024)
WingAnalogy is a computer tool for automated insect wing morphology and asymmetry analysis. It facilitates project management, enabling users to import pairs of wing images obtained from individual insects, such as left and right, fore- and hindwings. WingAnalogy employs image processing and computer vision to segment wing structures and extract cell boundaries, and junctions. It quantifies essential metrics encompassing cell and wing characteristics, including area, length, width, circularity, and centroid positions. It enables users to scale and superimpose wing images utilizing Particle Swarm Optimization (PSO). WingAnalogy computes regression, Normalized Root Mean Square Error (NRMSE), various cell-based parameters, and distances between cell centroids and junctions. The software generates informative visualizations, aiding researchers in comprehending and interpreting asymmetry patterns. WingAnalogy allows for dividing wings into up to five distinct wing cell sets, facilitating localized comparisons. The software excels in report generation, providing detailed asymmetry measurements in PDF, CSV, and TXT formats.
Keywords: Entomology; Fluctuating asymmetry; Analogy; PSO; Procrustes superimposition